Mapping antigenic sites on the major outer membrane protein of Chlamydia trachomatis with synthetic peptides. - Zhong, G M (1990)
The antigenicity of the major outer membrane protein (MOMP) of Chlamydia trachomatis was comprehensively evaluated by using overlapping hexapeptide homologs of serovar B MOMP and polyclonal rabbit antisera in a peptide enzyme-linked immunosorbent assay. Of 367 hexapeptides, 152 showed reactivities with at least one antiserum. Seven hexapeptides located within variable domain (VD) IV (residues 288 to 316) were found to be most reactive in terms of their binding titer and frequency, suggesting that VD IV is the immunodominant region within the MOMP as detected by this assay. Peptide-reactive antibodies could also recognize corresponding epitopes on either viable or acetone-permeabilized organisms. The antigenic specificity and immunoaccessibility of epitopes located in VD IV were resolved by absorbing antisera with chlamydial elementary bodies. Six antigenic sites were found in this region and included a B-type-specific site (S1), four subserogroup-specific sites (S2 and S4 to 6), and one species-specific site (S3), each displaying varying degrees of surface exposures on elementary bodies from different C. trachomatis serovars.